(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Uterine rupture is a catastrophic obstetric emergency defined by complete disruption of the uterine wall, including the serosa, leading to significant maternal and perinatal morbidity and mortality. While commonly associated with scarred uteri in the third trimester, atypical and unusual presentations are increasingly recognized, particularly in low-resource settings. These atypical manifestations often delay diagnosis and intervention, thereby worsening outcomes. Aim & Objectives: This study aims to highlight the spectrum of unusual presentations, associated risk factors, and clinical outcomes of uterine rupture cases managed at a tertiary care center. Material and Methods: A retrospective case series analysis was conducted in a tertiary care hospital in North Karnataka. Seven cases of uterine rupture were reviewed. Data were collected regarding demographic characteristics, obstetric history, clinical presentation, intraoperative findings, management strategies, and maternal and fetal outcomes. Cases included both scarred and unscarred uteri across different gestational ages. Results: Seven women aged 24–35 years were analyzed, including two primigravida and five multigravida with prior cesarean sections. Five ruptures occurred in the third trimester, while two occurred in the second trimester. All patients presented with acute abdominal pain; other symptoms included giddiness, vaginal bleeding, and signs of shock. Hemoperitoneum was observed in all cases. Mean hemoglobin was 6.1 g/dL. Six cases had absent fetal heart rate at presentation. Surgical management included four hysterectomies and three uterine repairs. Maternal survival was 100%, while perinatal mortality was 85.7%. Conclusion: This study underscores that uterine rupture may present atypically, including early gestation and in primigravida women. Delayed diagnosis significantly contributes to adverse fetal outcomes despite favorable maternal survival. Strengthening antenatal care, discouraging unskilled obstetric interventions, and improving early referral systems are essential to prevent such complications.